Possibilities : essays on hierarchy, rebellion, and desire - Graeber, David, 1961-2020 (Oakland, CA : AK Press, 2007)
Essays over hiërarchie, rebellie en verlangen.
Includes bibliographical references and index.
Keywords: Capitalism; Consumption (Economics).; Economic anthropology -- Philosophy; Hierachies -- Social aspects